(3QSGdI aj faj GdSgh Yf GdfHjs - (3GdYcHQj, GdMGQKj, GdHZOGOj, GdcQNj, CHh YHO Gddg, GdTjN GdoepajO, eMeO Hf eMeO Hf GdfYeGf Hf YHO GdSdGe, J (B413s ((3eMeO QVG Hf gGOj cGTa GdZWGAs)
(3ChdgG (B:s
(3GdMeO ddg GdPj GUWai eMeOG dQSGdJg(B... (3hHYO abO hbaJ CjgG GdCN(B... (3Ydi eG cJHJ Hg aj eYfi eG hLOJgs
(3BNQgG (B:s
(3hEf TjYjG jYJeO Ydi gPG GdMOjK aj GdMce Ydi GdfHj Udi Gddg Ydjg hSde hBdg HGdZdW hGdfbU(B... (3Edi Phj GdBaGJ GdeSbWI Yfge GdJcdja hGddg GdeSJYGf(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B696s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdJhMjO hGdedd hGdfMds